Boron foliar application, branch girdling and plant growth regulators on yield and fruit quality of ‘Garber’ pear trees - GIACOBBO,CLEVISON L. (2018)
ABSTRACT The aim of this study was to evaluate the influence of boron foliar application, branch girdling and plant growth regulators on the performance of pear trees cv. Garber. The experiment was arranged in a randomized block design with three replications. Treatments consisted of different boron rates (220, 440, 660 and 880 mL 100 L-1), branch girdling, and the plant growth regulators Promalin® (benzyladenine + gibberellins AG4+7) (560 mL 100 L-1) and Biozyme * TF (200 mL 100 L-1). The percentage of fruit set, stem length, fruit length, fruit diameter, flesh firmness, soluble solids and yield were assessed. The greatest fruit set was observed with Promalin® in both years and also boron and Biozyme * TF in the second year. The use of Promalin® increased peduncle length, fruit height but negatively affected soluble solids. Yield was also increased by this plant growth regulator and boron. Concluding, Promalin® improves fruit set, yield, and fruit quality and boron positively influence yield.